Systemic lupus erythematosus and pregnancy: Before gestation, during and after childbirth - T. M. Reshetnyak; N. M. Kosheleva; E. L. Nasonov (Научно-практическая ревматология)
Systemic lupus erythematosus (SLE) is a disease of women of reproductive age. Up to a certain time, pregnancy was contraindicated in patients with SLE, improving the management of the disease itself (monitoring), as well as understanding the safety of drugs make pregnancy possible for most patients with SLE. Careful pregnancy planning is crucial when the disease is well controlled with pregnancy-compatible medications. This is also facilitated by the management of patients jointly by doctors of different specialties (rheumatologist, neurologist, endocrinologist, etc.) with obstetricians. The article discusses the achievements of managing women with SLE during pregnancy planning, during pregnancy and after delivery.